How women's calling for science careers relates to psychological predictors of persistence in science - Reed, Kaitlyn A., author; Dik, Bryan J., advisor; Henry, Kim, committee member; Bloodhart, Brittany, committee member; Chavez, Ernest, committee member; Fischer, Emily, committee member (Colorado State University. Libraries, 2018)
Society is lacking numbers and diversity of trained scientists to address important key problems. Undergraduate women have been identified as a group that leaves the science-career pipeline at high rates (NSF, 2015), though researchers have highlighted science self-efficacy, identity, values, and intentions, as critical predictors of their persistence (Estrada et al., 2011). The current study proposes and investigates a new predictor of women's persistence in science: perceiving a calling as a scientist. Perceiving a calling predicts career development tasks and outcomes that are similar to known predictors of women's persistence in science (Hirschi, 2012). The present study explores if and how calling as a scientist relates to undergraduate women's science self-efficacy, identity as a scientist, interest in science, scientific community values, and intentions to pursue science. Bivariate correlations suggest perceiving a calling as a scientist is positively related to undergraduate women's science self-efficacy, identity as a scientist, prosocial values of the scientific community, and intentions to pursue science. Using Social Cognitive Career Theory (SCCT) as a framework, the hypothesis that the relationship between perceiving a calling as a scientist and intentions to pursue science is mediated by science self-efficacy and science identity (respectively) was supported. Explanations and implications of all investigated relationships are discussed. This study establishes calling as a new predictor, and SCCT as useful framework, for continued investigation of women's persistence in science.
Keywords: identity; social cognitive career theory; women in STEM careers; self-efficacy; calling; values